Opinia . pismo Ruchu Obrony Praw Człowieka i Obywatela, no. 22, 1979 - [ed. Andrzej Czuma et al.] ([s.n.], 1979)
Creation and circulation: Journal republished legally in 1990; Some numbers published in various versions, both single- and double-sided, also in 21 cm. format